High-efficiency trans-perovskite solar cell and preparation method thereof

Through the synergistic action of chemical passivation and field passivation, perovskite crystallization is regulated, and the problem of body phase and surface defects in perovskite solar cells is solved, achieving efficient photoelectric conversion and long-term stability.

CN119907603AActive Publication Date: 2025-04-29SHENZHEN MSU-BIT UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510086802.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Existing perovskite solar cells are prone to body phase and surface defects during crystallization, resulting in non-radiative recombination of carriers, affecting the efficiency and stability of the device.

Method used

By using polymer macromolecular materials for chemical passivation and small molecular materials for field passivation, perovskite crystallization is coordinated, and non-radiative recombination of carriers is inhibited, and effective passivation of perovskite body phase and interface is achieved.

Benefits of technology

It significantly improves the photoelectric conversion efficiency of perovskite solar cells and improves the long-term stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907603A_ABST
    Figure CN119907603A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite solar cells, in particular to a high-efficiency trans-perovskite solar cell and a preparation method thereof. The preparation method comprises the following steps: spin-coating a self-assembly monomolecular solution on a first region on the upper surface of a conductive substrate, and annealing to form a hole transport layer; spin-coating a perovskite precursor solution on the surface of the hole transport layer, dropwise adding a chemical passivation solution on the coated surface for annealing during spin-coating, spin-coating a field passivator solution on the surface of the annealed perovskite thin film, and annealing to form a perovskite active layer; spin-coating the surface of the perovskite active layer with a mixed solution of fullerene and a fullerene derivative, and spin-coating the surface of the perovskite active layer with an organic small molecule solution to form an electron transport layer; preparing electrodes on the electron transport layer and a second area on the upper surface of the conductive substrate; the chemical passivation solution is a polymer macromolecular material solution, and the field passivator solution is a micromolecule material solution. According to the high-efficiency trans-perovskite solar cell provided by the invention, the photoelectric conversion efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a high-efficiency inverted perovskite solar cell and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite solar cells (PSCs) have become a current research hotspot due to their excellent material properties. After just a few decades of development, their photoelectric conversion efficiency (PCE) has reached 26.7%.

[0003] In view of the ionic properties of perovskite materials, multiple defects will inevitably be generated in the bulk and surface of perovskite during the rapid crystallization process. In order to obtain efficient and stable perovskite cells, these defects in the bulk and surface should be passivated. At the same time, the bulk defects will slowly migrate to the surface of the perovskite film over time, and the interface defects of the perovskite film are 1-2 orders of magnitude more than the bulk defects. Therefore, while passivating the surface defects, the generation and migration of bulk defects should also be suppressed to minimize the non-radiative recombination of carriers to improve the efficiency and stability of the device.

[0004] Current studies have shown that bulk doping and interface engineering can reduce defects in perovskite films and improve the photoelectric conversion efficiency of PSCs. However, simultaneous optimization of bulk and interface is still required to improve the efficiency and stability of PSCs. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-efficiency inverted perovskite solar cell and a preparation method thereof. The perovskite is chemically passivated by using a polymer macromolecular material and field passivated by using a small molecule material. This method is simple to operate, low in cost and effective in effect. The perovskite crystallization can be regulated under the synergistic effect of chemistry and field, and the non-radiative recombination of carriers can be suppressed, thereby achieving effective passivation of the perovskite bulk phase and interface, greatly improving the photoelectric conversion efficiency of PSCs, and helping to improve the long-term stability of PSCs.

[0006] To this end, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a high-efficiency inverse perovskite solar cell in an optional embodiment, comprising the following steps:

[0008] S1: spin coating a self-assembled monomolecular solution on a first area on the upper surface of a conductive substrate, and annealing the coating layer to form a hole transport layer;

[0009] S2: Spin-coating a perovskite precursor solution on the surface of the hole transport layer, and during the spin-coating, dropping a chemical passivation solution on the coated surface, annealing once, and then spin-coating a field passivator solution on the surface of the perovskite film after the primary annealing, and annealing twice to form a perovskite active layer;

[0010] S3: spin coating a mixed solution of fullerene and fullerene derivatives on the surface of the perovskite active layer, and then spin coating an organic small molecule solution to form an electron transport layer;

[0011] S4: preparing metal electrodes on the electron transport layer and on the second region on the upper surface of the conductive substrate respectively;

[0012] Wherein, the chemical passivation solution is a polymer macromolecular material solution, and the field passivation agent solution is a small molecule material solution.

[0013] Preferably, the polymer macromolecular material in the polymer macromolecular material solution is a mixture of one or more of polyvinyl alcohol, poly(2-ethyl-2-oxazoline), polyethylene glycol and polyvinyl pyrrolidone; and / or the mass concentration of the polymer macromolecular material solution is 0.005-0.05 mg / mL; and / or the small molecule material in the small molecule material solution is a mixture of one or more of 3-aminomethylpyridine, phenethylamine iodide, phenethylammonium chloride and 1-phenylpyridine; and / or the volume concentration of the small molecule material solution is 0.5-5 μL / mL.

[0014] Specifically, the polymer macromolecular material is dissolved in chlorobenzene to obtain a solution with a mass concentration of 0.005-0.05 mg / mL, which is shaken at 20-30°C for 20-40 minutes, and filtered through a filter membrane with a pore size of 0.22 μm to obtain a polymer macromolecular material solution; the small molecule material is dissolved in chlorobenzene to obtain a solution with a volume concentration of 0.5-5 μL / mL, which is shaken at a temperature of 25-35°C for 10-30 minutes, and filtered through a filter membrane with a pore size of 0.22 μm to obtain a small molecule material solution.

[0015] Preferably, the self-assembled monomolecules in the self-assembled monomolecule solution are a mixture of one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid and 3,4,5-trimethoxybenzaldehyde; and / or, the mass concentration of the self-assembled monomolecule solution is 0.4-0.6 mg / mL; and / or, the conductive substrate is selected from one of fluorine-doped tin oxide transparent conductive glass, indium tin oxide transparent conductive glass, aluminum-doped zinc oxide transparent conductive glass, transparent indium tin oxide conductive film and transparent cadmium telluride conductive film.

[0016] Preferably, the solute of the perovskite precursor solution is a mixture of iodomethylamine, iodoformamidine, chloromethylamine, lead iodide and cesium iodide, and the solvent is one of N,N-dimethylformamide and dimethyl sulfoxide or a mixture of the two; and / or the concentration of the perovskite precursor solution is 0.8-1.5 mol / L.

[0017] Specifically, iodomethylamine, iodoformamidine, chloromethylamine, lead iodide and cesium iodide are dissolved in a solvent to prepare a solution with a concentration of 0.8-1.5 mol / L, and the solution is shaken at 27-40° C. for 6-12 hours, and filtered through a filter membrane with a pore size of 0.22 μm to obtain a perovskite precursor solution.

[0018] Preferably, the fullerene is C 60 and C 70 and / or the fullerene derivative is one of [6,6]-phenyl C61-butyric acid methyl ester and [6,6]-phenyl-C71-butyric acid isomethyl ester or a mixture of both; and / or the mass ratio of the fullerene derivative to the fullerene is 4-6:1; and / or the mass concentration of the mixed solution of the fullerene derivative and the fullerene is 15-30 mg / mL.

[0019] Preferably, the organic small molecule in the organic small molecule solution is one of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline and 4,7-diphenyl-1,10-phenanthroline or a mixture of the two; and / or the mass concentration of the organic small molecule solution is 0.5-1 mg / mL.

[0020] Preferably, in a high-efficiency inverted perovskite solar cell, the volume fraction of the self-assembled single molecule solution is 9-10 parts, the volume fraction of the perovskite precursor solution is 6-8 parts, the volume fraction of the chemical passivation solution is 18-22 parts, the volume fraction of the field passivator solution is 8-10 parts, the volume fraction of the mixed solution of fullerenes and fullerene derivatives is 1-3 parts, and the volume fraction of the organic small molecule solution is 8-12 parts.

[0021] Preferably, in step S1, the annealing time is 8-15min; and / or, in step S2, the time of the first annealing is 20-50min, and the time of the second annealing is 5-20s; and / or, when spin-coating the perovskite precursor solution, the spin-coating speed is 1000-6000rpm / min, and the time is 30-60s; and / or, when spin-coating the field passivator, the spin-coating speed is 3000-6000rom / min; and / or, in step S3, when spin-coating the mixed solution of fullerene and fullerene derivatives, the spin-coating speed is 3000-6000rpm / min; and / or, when spin-coating the organic small molecule solution, the spin-coating speed is 2000-5000rpm / min; and / or, in step S1 and step S2, the temperature of the annealing, the first annealing and the second annealing is 95-105°C, preferably 100°C.

[0022] Preferably, the metal electrode is prepared by vacuum evaporation; and / or, before step S1, it also includes a step of cleaning the conductive substrate.

[0023] Specifically, the conductive substrate is ultrasonically cleaned for 10-30 minutes with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol, respectively, and then dried, and then subjected to ultraviolet ozone treatment for 10-20 minutes for standby use;

[0024] In a second aspect, the present invention provides, in an optional embodiment, a high-efficiency inverted perovskite solar cell, comprising a conductive substrate, a hole transport layer, a perovskite active layer, an electron transport layer, and a metal electrode;

[0025] The hole transport layer is disposed in a first region on the upper surface of the conductive substrate;

[0026] The perovskite active layer is disposed above the hole transport layer;

[0027] The electron transport layer is disposed above the perovskite active layer;

[0028] The metal electrodes are respectively arranged on the second region of the upper surface of the conductive substrate and on the electron transport layer;

[0029] The perovskite active layer includes a chemical passivation material formed by a polymer macromolecular material solution and a field passivation material formed by a small molecule material solution.

[0030] Compared with the prior art, the present invention has one of the following beneficial effects:

[0031] 1. The present invention uses polymer macromolecular materials to chemically passivate perovskite and uses small molecule materials for field passivation. This method is simple to operate, low in cost, and effective. Under the synergistic effect of chemistry and field, perovskite crystallization can be regulated, non-radiative recombination of carriers can be suppressed, and effective passivation of the perovskite bulk phase and interface can be achieved, which greatly improves the photoelectric conversion efficiency of PSCs and helps to improve the long-term stability of PSCs.

[0032] 2. The method of the present invention is not only convenient, simple to operate, low-cost, and effective, but also the multiple defects in the perovskite bulk and surface are synergistically passivated, which inhibits the non-radiative recombination of carriers and improves the photoelectric conversion efficiency of PSCs.

[0033] 3. The present invention regulates the growth of perovskite crystals by acting on the perovskite bulk phase with polymer macromolecular materials to form larger perovskite grains. At the same time, the flexibility of small molecules on the perovskite surface interacts with uncoordinated lead ions on the perovskite surface to further regulate the perovskite surface energy level and form field passivation of the perovskite. This method realizes the performance regulation of the passivator in the preparation process of efficient trans-PSCs. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 The SEM images of the perovskite active layer in Example 2 and Comparative Example 3 of the present invention, wherein the Control group is the SEM image of the perovskite active layer of Comparative Example 3, and the Target group is the SEM image of the perovskite active layer of Example 2;

[0036] Figure 2 This is a schematic structural diagram of a high-efficiency inverse perovskite solar cell in Example 1 of the present invention;

[0037] Figure 3 This is a schematic diagram of the current-voltage test results in Example 2 of the present invention;

[0038] Figure 4 This is a schematic diagram of the current-voltage test results in Example 3 of the present invention;

[0039] Figure 5 This is a schematic diagram of the current-voltage test results in Example 4 of the present invention;

[0040] Figure 6 This is a schematic diagram of the current-voltage test results in Comparative Example 1 of the present invention;

[0041] Figure 7 This is a schematic diagram of the current-voltage test results in Comparative Example 2 of the present invention;

[0042] Figure 8 This is a schematic diagram of the current-voltage test results in Comparative Example 3 of the present invention;

[0043] Among them, 1-conductive substrate; 2-hole transport layer; 3-perovskite active layer; 4-electron transport layer; 5-metal electrode. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] In the following examples and comparative examples, the perovskite precursor solution is prepared as follows: iodomethylamine (23.8 mg), iodoformamide (219.3 mg), chloromethylamine (12.5 mg), lead iodide (760.7 mg), and cesium iodide (20 mg) are dissolved in a mixed solvent of N, N-dimethylformamide and dimethyl sulfoxide (the volume ratio of N, N-dimethylformamide and dimethyl sulfoxide is 4:1) to prepare a solution with a concentration of 1.2 mol / L, shaken at 27°C for 8 h, and filtered with a filter membrane with a pore size of 0.22 μm to obtain a perovskite precursor solution.

[0046] The preparation method of the chemical passivation solution is as follows: poly (2-ethyl-2-oxazoline) (PEOXA) is dissolved in chlorobenzene to obtain a solution with a mass concentration of 0.01 mg / mL, which is shaken at 25° C. for 25 minutes and filtered through a filter membrane with a pore size of 0.22 μm to obtain a polymer macromolecular material solution.

[0047] Preparation of field passivation agent solution: 3-aminomethylpyridine was dissolved in chlorobenzene to obtain a solution, which was shaken at 25° C. for 15 min and filtered through a filter membrane with a pore size of 0.22 μm to obtain a 3-aminomethylpyridine solution.

[0048] The technical solution of the present invention will be described below in conjunction with embodiments.

[0049] Example 1

[0050] See also Figure 2 , this embodiment provides a high-efficiency inverse perovskite solar cell, comprising a conductive substrate 1, a hole transport layer 2, a perovskite active layer 3, an electron transport layer 4 and a metal electrode 5;

[0051] The hole transport layer 2 is disposed on a first region of the upper surface of the conductive substrate 1;

[0052] The perovskite active layer 3 is disposed above the hole transport layer 2, and the perovskite active layer 3 includes a chemical passivation material formed by a polymer macromolecular material solution and a field passivation material formed by a small molecule material solution;

[0053] The electron transport layer 4 is disposed above the perovskite active layer 3;

[0054] The metal electrodes 5 are respectively arranged on the second region of the upper surface of the conductive substrate 1 and on the electron transport layer 4;

[0055] Wherein, the polymer macromolecular material is selected from one or more of polyvinyl alcohol (PVA), poly(2-ethyl-2-oxazoline) (PEOXA), polyethylene glycol (PEG) or polyvinyl pyrrolidone (PVP). In the present embodiment, the polymer macromolecular material is selected from poly(2-ethyl-2-oxazoline). The small molecule material is selected from one or more of 3-aminomethylpyridine, phenethylamine iodide, phenethylamine chloride or 1-phenylpyridine. In the present embodiment, the small molecule material is selected from 3-aminomethylpyridine.

[0056] Example 2

[0057] This embodiment provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0058] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0059] (2) 95 μL of a mixed solution of MeO-2PACz and Me-4PACz (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) with a concentration of 0.5 mg / mL was spin-coated on the first area on the upper surface of the conductive substrate, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0060] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer and spin-coated at a speed of 4500 rpm / min for 40 s. At the 32nd s of the total time, 200 μL of polymer macromolecular material solution (mass concentration of 0.01 mg / mL) was added as an anti-solvent. After the spin coating was completed, it was quickly transferred to a 100°C heating table for annealing for 35 min. Then, 90 μL of 3-aminomethylpyridine solution (concentration of 0.5 μL / mL) was spin-coated on the annealed perovskite film at a speed of 4000 rpm / min and immediately annealed at 100°C for 10 s to obtain a perovskite active layer. The microscopic results of the perovskite active layer were scanned using a scanning electron microscope. The results are shown in FIG. Figure 1 As shown in the Target group photo;

[0061] (4) Preparation of 20 mg / mL PC 61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60 The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0062] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0063] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 3The specific test results are shown in Table 1.

[0064] Example 3

[0065] This embodiment provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0066] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0067] (2) 95 μL of a mixed solution of MeO-2PACz and Me-4PACz (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) with a concentration of 0.5 mg / mL was spin-coated on the first area on the upper surface of the conductive substrate, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0068] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer, and spin-coated at a speed of 4500 rpm / min for 40 s. At the 32nd s of the total time, 200 μL of polymer macromolecular material solution (mass concentration of 0.01 mg / mL) was added as an anti-solvent. After the spin coating was completed, it was quickly transferred to a 100°C heating table for annealing for 35 min; then 90 μL of 3-aminomethylpyridine solution (concentration of 1 μL / mL) was spin-coated on the annealed perovskite film at a speed of 4000 rpm / min, and immediately annealed at 100°C for 10 s to obtain a perovskite active layer;

[0069] (4) Preparation of 20 mg / mL PC 61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60 The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0070] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0071] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 4 The specific test results are shown in Table 1.

[0072] Example 4

[0073] This embodiment provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0074] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0075] (2) 90 μL of a mixed solution of MeO-2PACz and Me-4PACz with a concentration of 0.5 mg / mL (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) is spin-coated on the first area on the upper surface of the conductive substrate by a spin coating method, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0076] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer, and spin-coated at a speed of 4500 rpm / min for 40 s. At the 32nd s of the total time, 200 μL of polymer macromolecular material solution (mass concentration of 0.01 mg / mL) was added as an anti-solvent. After the spin coating was completed, it was quickly transferred to a 100°C heating table for annealing for 35 min; then 90 μL of 3-aminomethylpyridine solution (concentration of 2 μL / mL) was spin-coated on the annealed perovskite film at a speed of 4000 rpm / min, and immediately annealed at 100°C for 10 s to obtain a perovskite active layer;

[0077] (4) Preparation of 20 mg / mL PC61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60 The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0078] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0079] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 5 The specific test results are shown in Table 1.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0082] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0083] (2) 95 μL of a mixed solution of MeO-2PACz and Me-4PACz (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) with a concentration of 0.5 mg / mL was spin-coated on the first area on the upper surface of the conductive substrate, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0084] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer, and spin-coated at a speed of 4500 rpm / min for 40 s. At the 32nd s of the total time, 200 μL of chlorobenzene solution was added dropwise. After the spin coating, the film was quickly transferred to a 100°C heating table for annealing for 35 min. Then, 90 μL of 3-aminomethylpyridine solution (concentration of 1 μL / mL) was spin-coated at a speed of 4000 rpm / min on the annealed perovskite film, and immediately annealed at 100°C for 10 s to obtain a perovskite active layer.

[0085] (4) Preparation of 20 mg / mL PC 61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60 The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0086] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0087] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 6 The specific test results are shown in Table 1.

[0088] Comparative Example 2

[0089] This comparative example provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0090] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0091] (2) 95 μL of a mixed solution of MeO-2PACz and Me-4PACz (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) with a concentration of 0.5 mg / mL was spin-coated on the first area on the upper surface of the conductive substrate, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0092] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer, and spin-coated at a speed of 4500 rpm / min for 40 s. At the 32nd s of the total time, 200 μL of polymer macromolecular material solution (mass concentration of 0.01 mg / mL) was added as an anti-solvent. After the spin coating was completed, it was quickly transferred to a 100°C heating table for annealing for 35 min to obtain a perovskite active layer;

[0093] (4) Preparation of 20 mg / mL PC 61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60 The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0094] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0095] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 7 The specific test results are shown in Table 1.

[0096] Comparative Example 3

[0097] This comparative example provides a method for preparing a high-efficiency inverse perovskite solar cell, comprising the following steps:

[0098] (1) ultrasonically cleaning a conductive substrate (fluorine-doped tin oxide transparent conductive glass) with a conductive substrate cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 12 minutes, drying the substrate, and then treating the substrate with ultraviolet ozone for 12 minutes for later use;

[0099] (2) 95 μL of a mixed solution of MeO-2PACz and Me-4PACz (the solvent is ethanol, and the mass ratio of MeO-2PACz to Me-4PACz is 1:1) with a concentration of 0.5 mg / mL was spin-coated on the first area on the upper surface of the conductive substrate, and annealed on a heating table at 100°C for 10 min to obtain a SAMs hole transport layer;

[0100] (3) 70 μL of perovskite precursor solution (concentration of 1.2 mol / L) was evenly spread on the SAMs hole transport layer and spin-coated at a speed of 4500 rpm / min for 40 s. After the spin coating, it was quickly transferred to a 100°C heating table for annealing for 35 min to obtain a perovskite active layer. The microscopic results of the perovskite active layer were scanned using a scanning electron microscope. The results are as follows: Figure 1 As shown in the photo of the Control group;

[0101] (4) Preparation of 20 mg / mL PC 61 BM and C 60 A mixed solution (the solvent is chlorobenzene, in which PC 61 BM and C 60The mass ratio of 4:1) was oscillated and ultrasonicated, and then filtered through a 0.22 μm pore size filter membrane. 20 μL of PC 61 BM and C 60 The mixed solution is spin-coated on the upper surface of the perovskite active layer at a spin-coating speed of 1500rpm / min, and then a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution (the solvent is isopropanol) with a concentration of 1mg / mL is prepared. After shaking, it is filtered through a filter membrane with a pore size of 0.22μm, and 100μL of the 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline solution is spin-coated at a spin-coating speed of 3000rpm / min. After completion, an electron transport layer is obtained;

[0102] (5) Place the multilayer film prepared in the above steps into a mask plate and place it in a vacuum deposition chamber. -5 After Pa, The silver electrode is evaporated to a thickness of The silver electrode is evaporated on the second region on the upper surface of the conductive substrate and on the electron transport layer to complete the preparation of a high-efficiency inverse perovskite solar cell. The structural schematic diagram of the high-efficiency inverse perovskite solar cell is shown in FIG. Figure 2 shown.

[0103] The prepared high-efficiency inverse perovskite solar cell was placed under standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, and use Keithley 2400 digital source meter to test. The current-voltage test results are as follows Figure 7 The specific test results are shown in Table 1.

[0104] Table 1 Test results of Examples 2-4 and Comparative Examples 1-3

[0105]

[0106]

[0107] pass Figure 3-8 It can be seen from Table 1 that the photoelectric conversion efficiency of perovskite solar cells is improved after using PEOXA chemical passivation and 3-aminomethylpyridine field passivation respectively, but after chemical passivation and field effect passivation at the same time, the photoelectric conversion efficiency of perovskite solar cells is significantly higher, so chemical and field synergy is an effective method for preparing high-performance inverse perovskite solar cells.

[0108] Although the principles of the present invention are described in detail above in conjunction with the preferred embodiments of the present invention, those skilled in the art should understand that the above embodiments are merely explanations of the exemplary implementations of the present invention, and are not intended to limit the scope of the present invention. The details in the embodiments do not constitute limitations on the scope of the present invention, and any obvious changes such as equivalent transformations, simple replacements, etc. based on the technical solution of the present invention, without departing from the spirit and scope of the present invention, fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-efficiency inverse perovskite solar cell, characterized in that: The following steps are involved: S1: spin coating a self-assembled monomolecular solution on a first area on the upper surface of a conductive substrate, and annealing the coating layer to form a hole transport layer; S2: Spin-coating a perovskite precursor solution on the surface of the hole transport layer, and during the spin-coating, dropping a chemical passivation solution on the coated surface, annealing once, and then spin-coating a field passivator solution on the surface of the perovskite film after the primary annealing, and annealing twice to form a perovskite active layer; S3: spin coating a mixed solution of fullerene and fullerene derivatives on the surface of the perovskite active layer, and then spin coating an organic small molecule solution to form an electron transport layer; S4: preparing metal electrodes on the electron transport layer and on the second region on the upper surface of the conductive substrate respectively; Wherein, the chemical passivation solution is a polymer macromolecular material solution, and the field passivation agent solution is a small molecule material solution.

2. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The polymer macromolecular material in the polymer macromolecular material solution is a mixture of one or more of polyvinyl alcohol, poly(2-ethyl-2-oxazoline), polyethylene glycol and polyvinyl pyrrolidone; and / or, The mass concentration of the polymer macromolecular material solution is 0.005-0.05 mg / mL; and / or, The small molecule material in the small molecule material solution is a mixture of one or more of 3-aminomethylpyridine, phenethylammonium iodide, phenethylammonium chloride and 1-phenylpyridine; and / or, The volume concentration of the small molecule material solution is 0.5-5 μL / mL.

3. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The self-assembled monomolecules in the self-assembled monomolecule solution are a mixture of one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid and 3,4,5-trimethoxybenzaldehyde; and / or, The mass concentration of the self-assembled monomolecular solution is 0.4-0.6 mg / mL; and / or, The conductive substrate is selected from one of fluorine-doped tin oxide transparent conductive glass, indium tin oxide transparent conductive glass, aluminum-doped zinc oxide transparent conductive glass, transparent indium tin oxide conductive film and transparent cadmium telluride conductive film.

4. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The solute of the perovskite precursor solution is a mixture of iodomethylamine, iodoformamidine, chloromethylamine, lead iodide and cesium iodide, and the solvent is one of N,N-dimethylformamide and dimethyl sulfoxide or a mixture of the two; and / or, The concentration of the perovskite precursor solution is 0.8-1.5 mol / L.

5. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The fullerene is C 60 and C 70 One or a combination of the following: and / or The fullerene derivative is one of [6,6]-phenyl C61-butyric acid methyl ester and [6,6]-phenyl-C71-butyric acid isomethyl ester or a mixture of the two; and / or, The mass ratio of the fullerene derivative to the fullerene is 4-6:1; and / or, The mass concentration of the mixed solution of the fullerene derivative and fullerene is 15-30 mg / mL.

6. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The organic small molecule in the organic small molecule solution is one of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline and 4,7-diphenyl-1,10-phenanthroline or a mixture of the two; and / or, The mass concentration of the organic small molecule solution is 0.5-1 mg / mL.

7. The method for preparing a high-efficiency inverse perovskite solar cell according to any one of claims 1 to 6, characterized in that: In a high-efficiency inverted perovskite solar cell, the volume fraction of the self-assembled single molecule solution is 9-10 parts, the volume fraction of the perovskite precursor solution is 6-8 parts, the volume fraction of the chemical passivation solution is 18-22 parts, the volume fraction of the field passivator solution is 8-10 parts, the volume fraction of the mixed solution of fullerenes and fullerene derivatives is 1-3 parts, and the volume fraction of the organic small molecule solution is 8-12 parts.

8. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: In step S1, the annealing time is 8-15 min; and / or, In step S2, the time of the first annealing is 20-50 minutes, and the time of the second annealing is 5-20 seconds; and / or, When spin coating the perovskite precursor solution, the spin coating speed is 1000-6000 rpm / min and the time is 30-60s; and / or, When the field passivating agent is spin-coated, the spin-coating speed is 3000-6000 rom / min; and / or, In step S3, when the mixed solution of fullerene and fullerene derivative is spin-coated, the spin-coating speed is 3000-6000 rpm / min; and / or, When spin coating the organic small molecule solution, the spin coating speed is 2000-5000 rpm / min; and / or, In step S1 and step S2, the temperatures of the annealing, the primary annealing and the secondary annealing are all 95-105°C.

9. The method for preparing a high-efficiency inverse perovskite solar cell according to claim 1, characterized in that: The metal electrode is prepared by vacuum evaporation; and / or, Before step S1, the method further includes a step of cleaning the conductive substrate.

10. A high-efficiency inverse perovskite solar cell, characterized in that: It includes a conductive substrate, a hole transport layer, a perovskite active layer, an electron transport layer and a metal electrode; The hole transport layer is disposed in a first region on the upper surface of the conductive substrate; The perovskite active layer is disposed above the hole transport layer; The electron transport layer is disposed above the perovskite active layer; The metal electrodes are respectively arranged on the second region of the upper surface of the conductive substrate and on the electron transport layer; The perovskite active layer includes a chemical passivation material formed by a polymer macromolecular material solution and a field passivation material formed by a small molecule material solution.

Citation Information

Patent Citations

  • Perovskite solar cell for passivating grain boundary defects and preparation method thereof

    CN115884610A

  • Inverse perovskite solar cell and preparation method thereof

    CN116669444A

  • Method for improving quality of perovskite thin film, perovskite thin film and solar cell

    CN119233734A